Tasks of the state policy of formation and implementation of social protection for persons with disabilities in Ukraine - Fomichov, Konstantyn (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to the study of the tasks of the state policy of formation and implementation of social protection of persons with disabilities in Ukraine. The article analyzes international and national legislation in the researched area. In the article, the author provides the author’s definition of the tasks of the state policy of the formation and implementation of social protection of persons with disabilities as a predetermined complex of decisions and actions of subjects of power, aimed at solving the problems of social protection of persons with disabilities. In addition, among the main tasks of social security of persons with disabilities recognized by the world community, namely the identification and elimination of obstacles and barriers that prevent the provision of rights and the satisfaction of needs, including access to public and civil facilities, improvement, transport infrastructure, road service (hereinafter – objects of the physical environment), transport, information and communication, as well as taking into account individual capabilities, abilities and interests – to education, work, culture, physical culture and sports; health care; social protection; ensuring the implementation of an individual rehabilitation program for persons with disabilities; provision of adapted housing; promotion of social activities. The author focuses on the fact that the inherited system of social protection of persons with disabilities is largely based on the medical model of disability. In addition, it was established that the issue of transition from the medical model of social protection is currently being updated, and currently the priority tasks of social protection of persons with disabilities are their autonomy and social inclusion; departure from the medical model of protection; the need to «transpose» the system of services for persons with disabilities, directing them to the independence and atomization of the individual.